Factors influencing treatment of veterans with advanced prostate cancer. Issue 13 (25th March 2021) - Caram, Megan E. V.; Burns, Jennifer; Kumbier, Kyle; Sparks, Jordan B.; Tsao, Phoebe A.; Chapman, Christina H.; Bauman, Jordan; Hollenbeck, Brent K.; Shahinian, Vahakn B.; Skolarus, Ted A.
Abstract : Background: Treatments for metastatic castration‐resistant prostate cancer (CRPC) differ in toxicity, administration, and evidence. In this study, clinical and nonclinical factors associated with the first‐line treatment for CRPC in a national delivery system were evaluated. Methods: National electronic laboratory and clinical data from the Veterans Health Administration were used to identify patients with CRPC (ie, rising prostate‐specific antigen [PSA] on androgen deprivation) who received abiraterone, enzalutamide, docetaxel, or ketoconazole from 2010 through 2017. It was determined whether clinical (eg, PSA) and nonclinical factors (eg, race, facility) were associated with the first‐line treatment selection using multilevel, multinomial logistic regression. The average marginal effects (AMEs) were calculated of patient, disease, and facility characteristics on ketoconazole versus more appropriate CRPC therapy. Results: There were 4998 patients identified with CRPC who received first‐line ketoconazole, docetaxel, abiraterone, or enzalutamide. After adjustment, increasing age was associated with receipt of abiraterone (adjusted odds ratio [aOR], 1.07; 95% credible interval [CrI], 1.06‐1.09) or enzalutamide (aOR, 1.10; 95% CrI, 1.08‐1.11) versus docetaxel. Greater preexisting comorbidity was associated with enzalutamide versus abiraterone (aOR, 1.53; 95% CrI, 1.23‐1.91). Patients with higher PSA values at the start of treatment were more likely to receive docetaxel than oral agents and less likely to receive ketoconazole than other oral agents. African American men were more likely to receive ketoconazole than abiraterone, enzalutamide, or docetaxel (AME, 2.8%; 95% CI, 0.7%‐4.9%). This effect was attenuated when adjusting for facility characteristics (AME, 1.9%; 95% CI, –0.4% to 4.1%). Conclusions: Clinical factors had an expected effect on the first‐line treatment selection. Race may be associated with the receipt of a guideline‐discordant first‐line treatment. Abstract : Clinical factors such as increasing age, comorbidities, and lower prostate‐specific antigen levels are associated with less toxic oral therapies as a first‐line treatment. African American men are more likely to receive ketoconazole as a first‐line treatment than other evidence‐based treatments, which is somewhat attenuated when adjusting for facility characteristics.